TAXONOMY OF MANNIA CONTROVERSA (MARCHANTIIDAE, AYTONIACEAE) INCLUDING A NEW SUBSPECIES FROM EAST ASIA - Schill, D. B.; Long, D. G.; Köckinger, H. (Edinburgh Journal of Botany, 2008)
Mannia controversa (Meyl.) Schill comb. nov. (Marchantiidae, Aytoniaceae), a long-forgotten European taxon, is fully redescribed and a lectotype selected. It is reported from its original localities in the Swiss Alps and new sites in the Austrian and French Alps. A series of specimens from eastern Asia are closely related and are described as Mannia controversa subsp. asiatica Schill & D.G.Long. For the species, differences with other Mannia species are summarised and for its two subspecies, descriptions, illustrations (including SEM images) and a key are provided along with notes on ecology and distribution maps.
Keywords: Aytoniaceae; liverworts; Mannia controversa; Marchantiidae; spore SEM; taxonomy